Ischemic stroke in young Asians caused by spontaneous cervical artery dissection may be due to slightly increased homocysteine - Lin, Zijun; Huang, Shuhan; Li, Wei (Frontiers in Neurology, 2025)
BackgroundSpontaneous cervical artery dissection (sCAD) is a non-atherosclerotic vascular disease among young and middle-aged individuals of unknown etiology that is recognized as a cause of ischemic stroke. Total plasma homocysteine (tHcy) is associated with an increased risk of sCAD, but the precise mechanism and level of tHcy remain unclear.MethodsFasting tHcy levels were determined in 296 patients with a first ischemic stroke due to sCAD (n = 159) and in age-/gender-matched hospital-based controls (n = 137) within 24 h after the onset of symptoms.ResultsThe mean age of sCAD patients with ischemic stroke and controls was 45.6 years; 61.0% of the cases and controls were male. The prevalence rates of hypertension, diabetes mellitus, and hyperlipidemia in sCAD patients were significantly increased. Fasting tHcy levels in sCAD patients were significantly higher (12.81 ± 5.24 μmol/L, 95% CI: 11.79–13.89) than those in controls (10.21 ± 3.33 μmol/L, 95% CI: 9.92–11.89, p < 0.001). Compared with the lowest homocysteine quartile, the quartile between 12.1 and 14.54 μmol/L was significantly associated with sCAD, with an adjusted odds ratio of 4.7. The adjusted odds ratio was 5.02 (95% CI: 1.91–13.39, p = 0.001) for every 1 μmol/L increase in log homocysteine according to the logistic regression model. Although sCAD occurred more often in winter than in other seasons (p = 0.02), tHcy levels in sCAD were not significantly different in terms of seasonal variation (p > 0.05).ConclusionOur results suggest that mildly increased tHcy may be a predisposing risk factor for ischemic stroke in young Asians caused by sCAD and that the relationship between them is significant; however, the precise mechanism requires further study. This result also supports the screening of fasting tHcy in young Asian adults for early intervention and control of tHcy levels, which plays an important role in early clinical prediction and intervention of sCAD.